Negative Pressure Pulmonary Edema in Ambulatory Setting: A Case Report - Monteiro, Catarina Torres; Coelho, Margarida Viana; Pereira, Luísa Helena; Portela, Inês; Jacob, Miguel; Gouveia, Alírio; Lares, Ana (Journal of the Portuguese Society of Anesthesiology, 2019)
The negative pressure pulmonary edema is an uncommon but potentially fatal complication, being more frequently reported following a significative inspiratory effort against an upper airway obstruction. Diverse risk factors have been identified and its knowledge is the cornerstone for an expeditous diagnosis and treatment, with severe impact on morbidity and mortality. This article reports a case of negative pressure acute pulmonary edema that occurred in a healthy male patient in the ambulatory setting.